Path Reinforcer or Policy Accelerator? COVID-19 and Scandinavian Social Protection Reform Trajectories - Bengtsson, Mattias; Høgedahl, Laust; Svalund, Jørgen (Nordic Journal of Working Life Studies, 2024)
A pandemic may change the use of social protection systems. In this article, we compare Scandinavian reform trajectories of unemployment benefits and sickness benefits following the COVID-19 pandemic. From an institutional theory perspective, we have analyzed official documents on regulations proposed in government bills, public inquiries, reports, and secondary literature published between March 2020 and December 2023, as well as interview data from key actors representing the state, the social partners, and related stakeholder organizations. The findings show that Denmark and Norway implemented mostly provisional reforms and thus ended in path reinforcement. In Sweden, on the contrary, numerous provisional reforms during the pandemic turned out to become permanent in the post-pandemic period. As the pandemic legitimized permanent changes that in some cases had been debated for a long time in Sweden, it thus came to act as a path-clearing policy accelerator.